2021
DOI: 10.3389/frwa.2021.597641
|View full text |Cite
|
Sign up to set email alerts
|

Diverging Water Ages Inferred From Hydrodynamics, Hydrochemical and Isotopic Tracers in a Tropical Andean Volcano-Sedimentary Confined Aquifer System

Abstract: Hydrogeology in the Andes cordillera reflects its complex geological history. In most cases, groundwater flows through fractures and faults that compartmentalize the volcanic material, and through the primary porosity of the volcano-sedimentary material. The volcanic mineral context and geothermal environment mark the groundwater chemistry, especially in the high concentrations of specific trace elements. This study focuses on the complex system of the Tumbaco – Cumbayá – Los Chillos aquifer, in the vicinity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…In the last decade, the demand for accurate spatio-temporal predictions of δ 2 H and δ 18 O values of rainfall at point, regional, and continental scales has increased [31], including the application of high-resolution in situ sampling of stable isotopes in the unsaturated zone, stream water, and rainfall [32,33], particularly by increasing and improving the amount of information in areas where few or no data exist, such as the tropics [34,35]. For example, stable isotopes of water have identified different altitudes for the recharge zone of the Chiche and Ilaló aquifers in Ecuador [36]. Similarly, [37] showed that the δ 2 H and δ 18 O stable isotope technique can be applied to hydrological models from local and regional to meso-global scales in China.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the demand for accurate spatio-temporal predictions of δ 2 H and δ 18 O values of rainfall at point, regional, and continental scales has increased [31], including the application of high-resolution in situ sampling of stable isotopes in the unsaturated zone, stream water, and rainfall [32,33], particularly by increasing and improving the amount of information in areas where few or no data exist, such as the tropics [34,35]. For example, stable isotopes of water have identified different altitudes for the recharge zone of the Chiche and Ilaló aquifers in Ecuador [36]. Similarly, [37] showed that the δ 2 H and δ 18 O stable isotope technique can be applied to hydrological models from local and regional to meso-global scales in China.…”
Section: Introductionmentioning
confidence: 99%